Analysis of Successful Offensive Patterns in Critical Moments in Men’s EuroBasket 2022 and Women’s 2021 - Christopher Vázquez-Estévez; Adrián Paramés-González; Iván Prieto-Lage; Xoana Reguera-López-de-la-Osa; Mónica Álvarez-Rodríguez; Alfonso Gutiérrez-Santiago (Applied Sciences)
The growing trend of analyzing all performance factors involved in a game makes identifying offensive patterns a determining factor in improving tactical performance and decision making during a game. The main objective of this research was to analyze the effectiveness and detect successful patterns on offense at critical moments in the men’s EuroBasket 2022 and women’s EuroBasket 2021. The sample was composed of 509 technical–tactical offensive actions obtained from the last 2 min of the final quarters and overtime from the group stage and final round, whose difference in the final score was equal to or less than five points. For this purpose, observational methodology was employed using LINCE PLUS software through an observational instrument designed ad hoc. Descriptive analysis and chi-square (χ2) tests were performed with SPSS 25, and a pattern analysis (T-Patterns) was performed with Theme 5 software. Statistical significance was set at p < 0.05. The teams that were losing when performing the offense finished a greater number of plays and with greater effectiveness. Fastbreaks seem to be more effective in the closing minutes, a play characterized by a maximum of three passes and by finishing with individual play such as 1 × 1. In turn, actions finished near the hoop by inside players seem to be more effective when the possession is finished before 17 s. The practical implications described in this research will enable coaches to tailor their strategies and training to the critical moments of the game.